Seeking the factors to stimulate the users in coastal zones planning. Case study: Open discussions with mussel farmers in the Axios river (GR) - ZANOU, B.; ANAGNOSTOU, CH.; PAPATHANASSIOU, E. (Mediterranean Marine Science, 2005)
In the framework of an integrated coastal zone management, the involvement of users is required and “open discussions” is one of the techniques used for their participation. The authors used this technique during a project for the sustainable development of mussel-culture in the coastal zone of the Axios Delta. Open discussion contributed to the acceptance of the scientific results by the users of the aquatic environment (mussel-farmers) who addressed trade-offs in their own way. The majority of their arguments were incorporated in the formation of the management rules, presented in the final report of this project. The present paper summarizes this experience as well as the existing ways for the involvement of users in a decision planning process and demonstrates how open discussion is a prerequisite factor for the success of sustainable development planning in Greece.